Other "Hamlet" in Puppet Theatre: A Contribution to Central European Theatre Diversity of the 1980s-1990s - Trefalt, Uroš (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This study aims to address the stigmatization and reductionism of Central European culture by many scholars and to decentralize it. At the Crossing Borders with Shakespeare Since 1945 conference, the roundtable discussion raised questions about naming and defining “Central Europe” and revealed several discrepancies. However, the discussion lacked cultural, political, and historical context. To address this, the author examines a lesser-known artistic genre, puppet theatre, for answers and comparisons. Zlatko Bourek, a Croatian artist and director, offers a unique perspective on the theatre of the 1980s and serves as an example of the diversity and heterogeneity of Central European cultural expression. Bourek’s work draws from the tradition of Central European puppetry and explores connections between the Iron Curtain and Yugoslavia. His artistic style is exemplified in his adaptation of Tom Stoppard’s play Fifteen-Minute Hamlet, which masterfully condenses the entire plot of William Shakespeare’s Hamlet into a fifteen-minute performance. Bourek’s concept of combining Shakespearean tragedy with farce, presented through Japanese traditional Bunraku theatre, represents an important experiment of the 1980s. The use of syncretism and the aesthetics of ugliness are notable features of this experiment. It is a breakthrough in the perceived history of puppet theatre for adults and an aesthetic experiment in the era of Central European totalitarianism.